PARTISIPASI MASYARAKAT DALAM PELESTARIAN LINGKUNGAN BERBASIS KOMUNITAS (Pelaksanaan Program Kali Bersih oleh Paguyuban Bendolole Asri di Kelurahan Kricak, Kecamatan Tegalrejo, Kota Yogyakarta) - , HERNITA OKTARINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Urbanization has both direct and indirect impact on the existence of the natural environment especially in cities. Oftenly, for some reasons, urban people make use of river basin area as their settlement area. Thus, pollution and damage to environment are inevitable. This research is aimed at analizing public participation on the implementation of the Clean River Program (Prokasih) at River Winongo. The researcher chose District Kricak as the location of the research on Prokasih implementation in Yogyakarta City. This area is managed under Paguyuban Bendolole Asri, a part of Forum Komunikasi Winongo Asri. The research method used in this research is qualitative perspective with case study research employing active public participation theory (Soetoro